Pemahaman Moderasi Beragama dalam Keluarga Melalui Pendidikan Kursus Pranikah di Kabupaten Bogor. - Fitriyani, Fitriyani; Hayaturrohman, Hayaturrohman; Latief, Tsabit (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
This research aims to provide an understanding of religious moderation to prospective brides through premarital courses in Rumpin Village with a research focus on the internalisation of religious moderation values to prospective brides through educational activities, premarital counseling, and understanding of Islamic teachings in the family environment in order to form a family that is appeasement (sakinah), love (mawaddah), affection (warahmah) and has moderate religious insight. This research is a field research with a sociological approach. Data collection techniques using documentation and observation, then analysed descriptively qualitative. The results showed that bridge-to-be in Rumpin Village in the premarital education held at the Religious Affairs Office were given religious knowledge material on how to settle down through moderate perspectives and attitudes. Moreover, the premarital education course is a programme of the Ministry of Religious Affairs which is carried out before the marriage contract is held. Islamic teachings remind us of the importance of knowledge in marriage.